Conjuring unseen forces: Rainmaking in Australia with John Henry Pepper. Issue 2 (1st October 2019) - Kent, Lynne
The climatic history of Australia records long periods of drought, with the late 1880s being particularly harsh, and the dry, hot conditions throughout the whole country led to drastic measures being taken. Those who believed in divine intervention looked to the heavens and prayed for rain while others considered scientific solutions. Purportedly scientific demonstrations of rainmaking in Australia during the late 1880s, accompanied by all the trappings of fairground entertainment, were attended by large crowds. Merry go-rounds, donkey rides and Punch and Judy puppet shows were enjoyed alongside 'gigantic electrical experiments' and other optical illusions. These experiments capitalized on the Victorian fascination for science, enjoyment of stage magic and the enduring desire to triumph over nature. This article discusses rainmaking, or pluviculture, as an entertainment in Australia in the late nineteenth century that walked the delicate line between magic and science. Whether through the use of new technologies or by evoking the powers of belief, conjuring the unseen forces of nature remains a powerful performative act that continues to resonate with audiences today.